On general representation of the meromorphic solutions of higher analogues of the second painleve equation - Gromak, V. I.; Stepanova, T. S. (Mathematical Modelling and Analysis, 1997)
“On general representation of the meromorphic solutions of higher analogues of the second painleve equation” Mathematical Modelling Analysis, 2(1), p.61-65.First Published Online: 14 Oct 2010